Estimation of the Prevalence of Antimicrobial Resistance in Badgers (Meles meles) and Foxes (Vulpes vulpes) in Northern Ireland - O’Hagan, Maria J. H.; Pascual-Linaza, Ana V.; Couzens, Catherine; Holmes, Clare; Bell, Colin; Spence, Nessie; Huey, Robert J.; Murphy, Julie A.; Devaney, Ryan; Lahuerta-Marin, Angela (Frontiers in Microbiology, 2021)
Antimicrobial resistant (AMR) bacteria can be shared between humans and animals, through food, water and the environment. Wild animals are not only potential reservoirs of AMR, but are also sentinels mirroring the presence of AMR zoonotic bacteria in the environment. In Northern Ireland, little is known about levels of AMR in bacteria in wildlife, thus the current study aimed to estimate the prevalence of AMR bacteria in wildlife using wildlife species from two ongoing surveys as a proxy. Nasopharyngeal swabs and faecal samples from European badgers (Meles meles) (146 faecal samples; 118 nasal samples) and red foxes (Vulpes vulpes) (321 faecal samples; 279 nasal samples) were collected throughout Northern Ireland and were used to survey for the presence of extended spectrum beta lactamase resistant and AmpC-type beta lactamases Escherichia coli (ESBL/AmpC), Salmonella spp. (only in badgers) and methicillin resistant Staphylococcus aureus (MRSA). ESBLs were detected in 13 out of 146 badger faecal samples (8.90%) and 37 out of 321 of fox faecal samples (11.53%), all of them presenting multi-drug resistance (MDR). Fourteen out of 146 (9.59%) badger faecal samples carried Salmonella spp. (S. Agama (n=9), S. Newport (n=4) and S. enterica subsp. arizonae (n=1)). Overall, AMR was found only in the S. enterica subsp. arizonae isolate (1/14, 7.14%). No MRSA were detected in nasopharyngeal swabs from badgers (n=118) and foxes (n=279). This is the first attempt to explore the prevalence of AMR in the two common wildlife species in Northern Ireland. These findings are important as they can be used as a base line for further research exploring the origin of the found resistance. These results should encourage similar surveys where environmental samples are included to bring better understanding of AMR dynamics, and the impact on wildlife, domestic livestock and humans.